2010
DOI: 10.2514/1.48462
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Fluid Jet Mixing at Supercritical Conditions

Abstract: Subcritical and supercritical fluids were injected in an inert gaseous atmosphere. Density distribution was measured and density-gradient profiles were inferred from the experimental data. A novel method was applied for the detection of detailed structures throughout the entire jet center plane. The core lengths were measured for each of the cases and correlated with previous visualization results. An eigenvalue approach was taken to determine the location of maximum gradients. The results show a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The details of the setup were given previously (Segal & Polikhov 2008;Roy & Segal 2010), hence only a brief description is included here. The high-pressure chamber shown in figure 1 is constructed to withstand pressures up to 70 atm and temperatures up to 600 K. The thermocouples and pressure transducers used had an accuracy of +1 K and +10 kPa, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the setup were given previously (Segal & Polikhov 2008;Roy & Segal 2010), hence only a brief description is included here. The high-pressure chamber shown in figure 1 is constructed to withstand pressures up to 70 atm and temperatures up to 600 K. The thermocouples and pressure transducers used had an accuracy of +1 K and +10 kPa, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The notable studies investigated the behavior of subcritical fluoroketone round jet injected into chamber conditions that varied from subcritical to supercritical. 11,12 The studies showed that the jet exhibited supercritical behavior with no droplet formation beyond the critical pressure and temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Under transcritical conditions mass transfer from the dense oxygen stream to the lighter surrounding flow is essentially governed by turbulent production of surface area, generation of strained layers of dense fluid and mixing. This particular mixing process was observed and intensively analyzed in a number of experimental studies on cryogenic injection at high-pressure performed at AFRL [7,8] and DLR [9][10][11][12][13], and more recently at the University of Florida [14,15].…”
Section: Introductionmentioning
confidence: 99%